2015
DOI: 10.1371/journal.pone.0139935
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of C57BL/6 Mice by a Potential Probiotic Bifidobacterium bifidum Strain under Germ-Free and Specific Pathogen-Free Conditions and during Experimental Colitis

Abstract: The effects of at least some probiotics are restricted to live, metabolically active bacteria at their site of action. Colonization of and persistence in the gastrointestinal tract is thus contributing to the beneficial effects of these strains. In the present study, colonization of an anti-inflammatory Bifidobacterium bifidum strain was studied in C57BL/6J mice under germ-free (GF) and specific pathogen-free (SPF) conditions as well as during dextran sulfate sodium (DSS)-induced colitis. B. bifidum S17/pMGC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 59 publications
3
36
0
Order By: Relevance
“…In contrast, P. UF1 permanently colonized the gut of germfree (GF) mice, as detected in the fecal contents of these mice until day 7 ( Figure 2E). Such colonization in GF mice was expected, as P. UF1, like other beneficial (e.g., Bifidobacterium bifidum) (17) or pathogenic bacteria (e.g., Citrobacter rodentium) (18), demonstrates the same trend due to the lack of competitive commensal bacteria.…”
Section: Characterization Of P Uf1 Bacteriummentioning
confidence: 63%
“…In contrast, P. UF1 permanently colonized the gut of germfree (GF) mice, as detected in the fecal contents of these mice until day 7 ( Figure 2E). Such colonization in GF mice was expected, as P. UF1, like other beneficial (e.g., Bifidobacterium bifidum) (17) or pathogenic bacteria (e.g., Citrobacter rodentium) (18), demonstrates the same trend due to the lack of competitive commensal bacteria.…”
Section: Characterization Of P Uf1 Bacteriummentioning
confidence: 63%
“…Myricetin (purity >95%) was purchased from the National Institutes for Food and Drug Control (Beijing, China) and dissolved in water. For the induction of acute experimental colitis, the mice were exposed to 2% DSS for consecutive 7 days …”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that the effects of bifidobacteria are only exerted, or are increased, when live bifidobacteria are used. Grimm et al [64] showed that the beneficial effects of B. bifidum S17 in DSS colitis were seen from only live and not UV-killed bacteria, and Hsieh et al [57] showed that only live B. bifidum had a restorative effect on a TJ impaired Caco-2 cell monolayer. They found that acetate and formate were produced more by B. bifidum than by B. adolescentis.…”
Section: Epithelial Cellsmentioning
confidence: 99%